1999
DOI: 10.1007/s002340050851
|View full text |Cite
|
Sign up to set email alerts
|

Rathke's cleft cyst with pituitary apoplexy: case report

Abstract: bACKgROUND: Tetrasomy X is a rare chromosomal aneuploidy seen in girls, associated with facial dysmorphism, premature ovarian insufficiency and intellectual disability. A Rathke's cleft cyst (RCC) is a remnant of Rathke's pouch which may cause multiple pituitary hormone deficiencies by exerting pressure on the pituitary gland in the sella. MeTHODS/ReSUlTS: The patient was diagnosed with tetrasomy X by karyotyping during infancy. brain MRI and multiple endocrine stimulation tests revealed RCC and combined pitui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…In our study, the median duration of symptoms was 12 months, ranging between 0.25 and 120 months; this is in accord with previously published data, in which the mean duration of symptoms/signs was 9-24 months (4,12,14,16). Notably, an acute presentation mimicking pituitary apoplexy was found in three of our patients; similar cases have been infrequently described (14,17,18). Headache was the most common clinical feature at presentation (67%), in accord with previously reported studies (55-81%) (4,11,13,14,16,(19)(20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the median duration of symptoms was 12 months, ranging between 0.25 and 120 months; this is in accord with previously published data, in which the mean duration of symptoms/signs was 9-24 months (4,12,14,16). Notably, an acute presentation mimicking pituitary apoplexy was found in three of our patients; similar cases have been infrequently described (14,17,18). Headache was the most common clinical feature at presentation (67%), in accord with previously reported studies (55-81%) (4,11,13,14,16,(19)(20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 92%
“…The differential diagnosis of a hemorrhagic suprasellar mass includes Rathke cleft cyst [1][2][3][4], craniopharyngioma [5,6], optic or hypothalamic glioma [7][8][9][10][11][12], cavernous angioma [13], venous angioma [14,15], germinoma [16], meningioma [17][18][19], and aneurysm. We describe the first reported case of pituicytoma presenting with spontaneous hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Although it tends to be associated with large adenomas, particularly with prolactinomas, it can be associated with any adenomas and, rarely, with nonadenomatous pituitary gland and other lesions [1][2][3]. Despite its uncertain pathogenesis, pathological study has shown that nearly equal numbers have resulted from pure clot, hemorrhagic infarction, and bland infarction [4].…”
mentioning
confidence: 99%